High‐fat diet triggers Mallory‐Denk body formation through misfolding and crosslinking of excess keratin 8. Issue 1 (27th May 2014) - Kucukoglu, Ozlem; Guldiken, Nurdan; Chen, Yu; Usachov, Valentyn; El‐Heliebi, Amin; Haybaeck, Johannes; Denk, Helmut; Trautwein, Christian; Strnad, Pavel
<x xml:space="preserve">Abstract</x> Mallory‐Denk bodies (MDBs) are protein aggregates consisting of ubiquitinated keratins 8/18 (K8/K18). MDBs are characteristic of alcoholic and nonalcoholic steatohepatitis (NASH) and discriminate between the relatively benign simple steatosis and the more aggressive NASH. Given the emerging evidence for a genetic predisposition to MDB formation and NASH development in general, we studied whether high‐fat (HF) diet triggers MDB formation and liver injury in susceptible animals. Mice were fed a high‐fat (HF) or low‐fat (LF) diet plus a cofactor for MDB development, 3, 5‐diethoxycarbonyl‐1, 4‐dihydrocollidine (DDC). Additionally, we fed nontransgenic and K8 overexpressing mice (K8tg) with the HF diet. The presence of MDB and extent of liver injury was evaluated using biochemical markers, histological staining, and immunofluorescence microscopy. In DDC‐fed animals, an HF diet resulted in greater liver injury and up‐regulation of inflammation‐related genes. As a potential mechanism, K8/K18 accumulation and increased ecto‐5′‐nucleotidase (CD73) levels were noted. In the genetically susceptible K8tg mice, HF diet triggered hepatocellular injury, ballooning, apoptosis, inflammation, and MDB development by way of 1) decreased expression of the major stress‐inducible chaperone Hsp72 with appearance of misfolded keratins; 2) elevated levels of the transglutaminase 2 (TG2); 3) increased K8 phosphorylation at S74 with subsequent TG2‐mediated crosslinking of phosphorylated K8; and 4) higher production of the MDB‐modifier gene CD73. Conclusion: Our data demonstrate that HF diet triggers aggregate formation and development of liver injury in susceptible individuals through misfolding and crosslinking of excess K8. (Hepatology 2014;60:169–178)